STRATEGI DINAS SOSIAL KOTA MEDAN DALAM MENERAPKAN KODE ETIK JURNALISTIK PADA POSTINGAN SOSIAL MEDIA (INSTAGRAM) - Reza Suhendri Tarigan; Tuan M. Yoserizal Saragih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The Medan City Social Service is one of the Medan city government agencies that uses social media Instagram as a medium for presenting the information they have and reporting to the public. In presenting this information. The Medan City Social Service must pay attention to and implement the form of a journalistic code of ethics in Instagram posts as a form of social responsibility and professionalism. Some of the ethical codes that are considered are presenting true and accurate information, reflecting fairness, maintaining privacy rights, protecting copyrights, maintaining objectivity in presenting them and having respect for related parties. The research method used in writing this journal article is a descriptive qualitative research method by producing research related to how the Medan City Social Service has a strategy in implementing the Journalistic Code of Ethics on their Instagram posts.